Freedom Fighter and Location: a Different Story of Partisan Commander Petras Bartkus - Petrauskienė, Aistė (Genocidas ir rezistencija, 2016)
The subject of the research in this article is the locations of the partisan warfare determined by the historical events of mid-20th century. The main aim of the research is to highlight the diversity and abundance of the locations of the partisan warfare based on the field data, oral history, archival documents and historical literature. In order to outline the significance of these locations, the case of Petras Bartkus, member of the presidium of the Council of the Movement of the Struggle for Freedom of Lithuania, was selected. The story starts at his birthplace in Pakapurnys Village (Raseiniai District) in 1925 and ends in 1991 in the cemetery of the town of Radviliškis, where the remains of those who had perished in Užpelkių Forest on 13 August 1949 were buried.The partisan warfare theatre connects various locations of the partisan warfare and allows us to speak about a coherent and homogeneous theatre rather than its individual episodes (bunkers and individual locations of the battles, places of death, etc.). Within the area divided by the war, some locations with encoded values and memories about them emerged, which have been included in the general narrative of the fights for freedom and stand out as places of historical memory.Archival and field studies make it possible to expand and provide more details to the space in which Bartkus operated, and subsequently to bring people back into the coherent historical partisan warfare narrative. The text lists the locations visited by Bartkus (and there are certainly more of them) and their diversity and abundance supports the thought that the landscape of freedom fights has been unduly diminished. The text mentions 37 places which are better known or which have been identified and 10 more general places, most of which are directly linked to Bartkus’ activities. They can be allocated to 13 different groups, such as his birthplace, camps, bunkers, shelters, locations of the archives, farmsteads of supporters, contact points, places of meetings, battles, places of death and desecration of dead bodies, and places of burial.Bartkus’ case study brings back an important perception of space during the years of the partisan war, which, after the restoration of an independent state, was generally reduced to the perception consisting of the places of death and burial. A rather comprehensive discussion of Barkus’ life provides supporting details to the environment in which freedom fighters operated, diversity of locations, their change depending on the person’s rank and time of operational activities. Bartkus’ example shows that the perception of the locations of the partisan warfare, which have so far been described as possible locations, but not necessarily existing locations, should be reconsidered. Where possible, the priority should be given to partisan documents, oral history, and field studies, while the documents of the Soviet security structures must be used for the search of additional information.
Keywords: Lithuania; Soviet occupation; partisans; commemoration